Effect of participation in a randomised controlled trial of an integrated palliative care intervention on HIV-associated stigma. Issue 9 (2nd September 2018) - Lowther, Keira; Harding, Richard; Simms, Victoria; Gikaara, Nancy; Ahmed, Aabid; Ali, Zipporah; Kariuki, Hellen; Sherr, Lorraine; Higginson, Irene J; Selman, Lucy
ABSTRACT: We conducted in Kenya a mixed-methods randomised controlled trial (RCT) of a nurse-led palliative care intervention integrated with anti-retroviral therapy (ART) provision for the management of HIV. Here we report qualitative findings showing increased resistance to HIV-associated stigma among trial participants. A mixed method design was chosen to enable identification of the active ingredients of the intervention and exploration of participants' experiences of receiving the intervention. The RCT was conducted from July 2011 to November 2012 in a community hospital in the city of Mombasa, Kenya, with a sample of 120 adults with HIV on ART. Thirty participants were purposively selected to take part in a qualitative exit interview, based on study arm and mental health outcome. Inductive thematic analysis revealed increased resistance to HIV-associated stigma in both the intervention and control groups. Specifically, patients in both groups described benefit from the social support, compassionate care, and open and respectful communication they received through study participation. Participants described improved self-image, increased access to social agency, and increased resistance to HIV-associated stigma. Our findings suggest that there is potential to increase resistance to stigma through simple mechanisms of support, compassion, and improved communication in routine care. The self-reported impact of trial participation on stigma also has implications for future trials in populations in resource-constrained settings where stigma is common.